Wiersz, czyli sytuacja rzeźbiarska O materialności Kordu Natalii Malek - Trzeciak, Katarzyna (Śląskie Studia Polonistyczne, 2018)
The article is an attempt at providing an interpretation of Natalia Malek’s work Kord in the context of sculpture and materiality. Starting from outlining a definition of a sculpture as a situation and a meeting, the author tries to demonstrate how a poetical language stages the sculptural, departing from the tradition of concrete poetry in favour of openness and potentiality of a poem. The essential contexts for the following argument are both elements of the study of objects and the feminist approach to corporality, which stimulate thinking in terms of the matter and materiality and enable us to interpret Malek’s project as addressing dualisms of Western metaphysics, as well as calling for a different type of reading. The category of “material vision” (de Man) is for the author of the article a point of departure, however, in result, it turns out to be insufficient and gives way to the project of reading understood as a “sculptural situation”.